Studi Kasus : Penerapan Pursed Lip Breathing untuk Meningkatkan Saturasi Oksigen pada Klien Efusi Pleura dengan Masalah Keperawatan Pola Napas Tidak Efektif - Adinda Dwi Putri; Nonok Karlina; Muadi Muadi (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2026)
Pleural effusion is a condition characterized by the accumulation of excess fluid in the pleural cavity, which may cause impaired lung expansion, decreased ventilation, dyspnea, and reduced oxygen saturation. This condition often leads to the nursing problem of ineffective breathing pattern, requiring prompt management to maintain adequate oxygenation. One of the non-pharmacological interventions that can be applied is the Pursed Lip Breathing (PLB) technique, a breathing exercise aimed at improving lung ventilation, reducing shortness of breath, and increasing oxygen saturation. The purpose of this case study was to determine the application of Pursed Lip Breathing in improving oxygen saturation in a patient with pleural effusion experiencing an ineffective breathing pattern at Rosella Ward, Kardinah Regional General Hospital, Tegal City. The method used was a case study approach based on the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. Data were collected through interviews, observation, physical examination, and documentation. The subject of this study was one patient diagnosed with pleural effusion who experienced an ineffective breathing pattern. The Pursed Lip Breathing intervention was administered for three consecutive days, with a duration of 5–10 minutes per session according to the patient's tolerance. The results showed an improvement in the patient's respiratory status after the implementation of Pursed Lip Breathing. The patient experienced a reduction in dyspnea, respiratory rate approached the normal range, the use of accessory respiratory muscles decreased, and oxygen saturation increased compared to the pre-intervention condition. In addition, the patient appeared more relaxed and comfortable while breathing. In conclusion, the application of Pursed Lip Breathing was effective in improving oxygen saturation and breathing patterns in a patient with pleural effusion and an ineffective breathing pattern. This intervention can be considered a simple, safe, and effective non-pharmacological nursing intervention to support patients' oxygenation needs.